Friendship's death - Pheloung, Barrington Somers 1954-2019 (British Film Institute, 2021)
"In Amman in Jordanien, zur Zeit des "Schwarzen September" im Jahr 1970, als die Jordanier die Palästinenser töten oder vertreiben, begegnet ein englischer Journalist, Sympathisant der PLO, einer Außerirdischen, die durch ein Mißgeschick statt am Technologie-Institut in Massachusetts in Amman landet. Ein kurioser Diskurs über Politik und Science-fiction; mit avantgardistischen und fabulierfreudig-philosophischen Mitteln gestalteter essayistischer Disput um politische und individuelle Moral." [filmdienst.de]
Original: Großbritannien 1987
special features: remastered in 4K by the BFI National Archive ; newly recorded audio commentary with producer Rebecca O’Brien, cinematographer Witold Stok and BFI curator Josephine Botting ; "Reflections on 'Friendship's death'" (2020, 40 mins): Tilda Swinton, Bill Paterson, Rebecca O'Brien and Witold Stok join BFI curators Will Massa and Josephine Botting to talk about "Friendship's death" ; "Peter Wollen - writing, politics, film" (2020, 63 mins): academics and filmmakers' Laura Mulvey and Kodwo Eshun join BFI archivist Wendy Russell for an appreciation of the work of Peter Wollen ; "Frida Kahlo & Tina Modotti" (1983, 30 mins): documentary by Laura Mulvey and Peter Wollen exploring the work of painter Frida Kahlo and photographer Tina Modotti, women icons of the Mexican Renaissance. It features footage of Modotti in the 1920 Hollywood film "The tiger's coat" and some exquisite home movie shots of Frida Kahlo and muralist Diego Rivera ; newly created French subtitles (feature only)
Keywords: Film